Application of a Stability-Indicating HPTLC Method for Simultaneous Quantitative Determination of Olmesartan Medoxomil and Hydrochlorothiazide in Pharmaceutical Dosage Forms - Kaliappan Ilango; Pushpangadhan S. Shiji Kumar (Journal of Analytical Methods in Chemistry)
A rapid, precise, sensitive, economical, and validated high performance thin layer chromatographic method is developed for simultaneous quantification of olmesartan medoxomil and hydrochlorothiazide in combined tablet dosage form. The method used amlodipine as internal standard (IS). Chromatographic separations were achieved on silica gel 60 F254 plates using toluene-methanol-ethyl acetate-acetone (2.5 : 1 : 0.5 : 2, v/v/v/v) as mobile phase. Densitometric analysis was carried out in the reflectance mode at 258 nm. Calibration curves were linear over a range of 80–480 ng/band for olmesartan medoxomil and 25–150 ng/band for hydrochlorothiazide. The detection and quantification limits were found to be 18.12 and 56.35 ng/band for olmesartan medoxomil and 6.31 and 18.56 ng/band for hydrochlorothiazide, respectively. Intra- and interassay precision provided relative standard deviations lower than 2% for both analytes. Recovery from 99.60 to 101.22% for olmesartan medoxomil and 98.30 to 99.32% for hydrochlorothiazide show good accuracy. Both the drugs were also subjected to acid, alkali, oxidation, heat, and photodegradation studies. The degradation products obtained were well resolved from pure drugs with significantly different values. As the method could effectively separate the drugs from their degradation products, it can be used for stability-indicating analysis. Validation of the method was carried out as per international conference on harmonization (ICH) guidelines.